Inequity in care delivery in cardio-oncology: dissecting disparities in underrepresented populations - Patel, Shruti Rajesh; Suero-Abreu, Giselle Alexandra; Ai, Angela; Ramachandran, Maya K.; Meza, Kelly; Florez, Narjust (Frontiers in Oncology, 2023)
It is well known that patients with cancer have a significantly higher cardiovascular mortality risk than the general population. Cardio-oncology has emerged to focus on these issues including risk reduction, detection, monitoring, and treatment of cardiovascular disease or complications in patients with cancer. The rapid advances in early detection and drug development in oncology, along with socioeconomic differences, racial inequities, lack of support, and barriers to accessing quality medical care, have created disparities in various marginalized populations. In this review, we will discuss the factors contributing to disparities in cardio-oncologic care in distinct populations, including Hispanic/Latinx, Black, Asian and Pacific Islander, indigenous populations, sex and gender minorities, and immigrants. Some factors that contribute to differences in outcomes in cardio-oncology include the prevalence of cancer screening rates, genetic cardiac/oncologic risk factors, cultural stressors, tobacco exposure rates, and physical inactivity. We will also discuss the barriers to cardio-oncologic care in these communities from the racial and socioeconomic context. Appropriate and timely cardiovascular and cancer care in minority groups is a critical component in addressing these disparities, and there need to be urgent efforts to address this widening gap.